MANAJEMEN PEMASARAN HOTEL SYARIAH DENGAN PENDEKATAN MAQASHID SYARI’AH (Studi Pada Hotel Syariah di Solo) - Azidni Rafiqo' (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2019)
The purpose of this study is to look at sharia business management (Syariah Hotel Solo) with the maqoshid Syariah approach. Maqoshid sharia is the right measurement tool to see the success of a religion-based business. The research method used is qualitative with the approach of maqoshid sharia. The analysis used is descriptive analysis. The data used are primary and secondary data. The results of this study indicate that Sharia Hotels have implemented maqoshid sharia by showing activities and management in accordance with maqoshid. The limitation of this study is to only use maqoshid syariah descriptively. The suggestion for further research is that research can be developed with hotels based on sharia and can use definite measuring instruments, such as the maqoshid syariah index.